In situ electron microscopy: atomic-scale dynamics of metal oxidation and corrosion - Zhikang Zhou; Xiaobo Chen; Dongxiang Wu; Dingding Zhu; Jianmin Chen; Xianhu Sun; Meng Li; Canying Cai; Judith C. Yang; Guangwen Zhou (npj Materials Degradation)
Abstract Corrosion degrades metals through complex microscopic processes that traditional methods often fail to capture. In situ transmission electron microscopy (TEM) bridges this gap by providing real-time, atomic- and nanoscale imaging of oxidation and corrosion dynamics. Gas-phase TEM uncovers critical oxidation mechanisms like oxide nucleation and alloying effects, while liquid-phase TEM tracks corrosion initiation. Coupled with emerging techniques like ultrafast direct electron detection cameras, these advancements promise unprecedented resolution in understanding material degradation.